Digital Transformation of Islamic Endowments (Waqf): What Appeals to Generation Z in e-Cash Waqf? - Canggih, Clarashinta; Imron Mawardi; Zaimy Johana Johan; Yan Putra Timur (Universitas Airlangga, 2025)
Background: Cash waqf in Indonesia is optimized through the use of digital media to improve access, transparency, and public participation, particularly among the tech-savvy younger generation. This led to the formulation of effective strategies, which enabled the understanding of factors influencing digital waqf intention, including gender-based differences. Objective: This present study aims to explore gender differences in respect to the determinants of intention towards participating in digital cash waqf. This was realized by comparing responses between male and female Generation Z individuals. Methods: This quantitative study adopted purposive sampling method to collect data. Subsequently, a total of 645 respondent data were processed using Partial Least Square Structural Equation Model (PLS-SEM) method with the assistance of SmartPLS 4.0 software. Results: The male and female respondents stated that cash waqf literacy did not influence trust and behavioral intention. However, perceived ease of e-cash waqf significantly impacted both trust and behavioral intention. Majority of the male respondents reported that religiosity, and trust in nazhir had a significant impact. Both genders stated that religiosity did not moderate the relationship between the variables. Conclusion: In conclusion, the importance of technological ease of use and religiosity in influencing trust and intention to contribute to digital cash waqf was analyzed. Based on this perspective, both variables impacted trust and behavioral intention. The female respondents perceived trust as an insignificant factor, and recommended nazhir institutions partnered with financial technology (fintech) companies to develop user-friendly platforms. This included the engagement of female donors through religious education. The numerous campaigns should focus on technological literacy and the religious value of digital waqf contributions. Keywords: E-cash waqf, Generation Z, Multi Group Analysis, Male, Female